A study on sodalite pellets as matrix for spent chloride salts confinement. Issue 63 (20th February 2017) - Capone, M.; Fedeli, C.; De Angelis, G.; Da Ros, M.; Giacobbo, F.; Giola, M.; Macerata, E.; Mariani, M.
ABSTRACT: Pellets made of pure sodalite blended with commercial glass frit and pellets made of sodalite, glass frit and a mixture of chloride salts, synthesized through dry pressing and subsequent thermal treatment, were evaluated as a potential matrix for confinement of spent chloride salts coming from pyroprocesses. The sodalite pellets were leached at 23°C and 90°C for 28 days, according to the ASTM C1220-10 procedure. Normalized release rates were estimated for the following elements: Li, Na, Al, Si, K, Rb, Cs, Sr, Ba, La, Nd and compared with literature results. SEM investigations, carried out before and after the leaching tests, show dissolution and re-precipitation phenomena at 90°C.